RESOLUTION OF TORT DISPUTES IN THE IMPLEMENTATION OF AKAD AL-QARDH IN SHARIA BANKING - Tin Yuliani (Journal of Islamic Business and Economic Review, 2020)
This article focuses on Akad Qard as one of the Akad in sharia banking. At Qard, financing can be a possible occurrence of potential disputes between borrowers and the lending party. In terms of normative, dispute resolution arrangement, in case of default, is stipulated in Law No. 21 of 2008 on Sharia banking. Default dispute resolution mechanisms are multi-fascinated, depending on the right choice of the parties. Using normative research methods with of approach and conceptual approach is further analyzed descriptively analytical. The research results that, the settlement of default to the financing of Akad al-Qardh in customers who have since the beginning of good faith, is first a non-litigation solution by the principles of's Consultative and justice. Sharia banks make restructuring efforts based on the financing agreement agreed upon by the parties. If the restructuring efforts do not bring results, sharia banks can conduct a guarantee execution effort. In the Akad al-Qard with guarantees or without warranty, the default dispute carried out through the National Sharia Arbitration Board on a litigation basis, or it can be attempted by voluntary customers to submit collateral. In addition to the mandate of Article 55 paragraph (1) of the sharia banking LAW, which determines that it authorizes the impartial judiciary as a form of litigation dispute resolution for the completion of the first form, the new settlement of non-litigation.